Performance of trees and crops under organic manure treatments in Populus deltoides and Melia composita based agroforestry system - Gill, Rishi I.S.; Kaur, Navneet; Singh, Baljit (Indian Journal of Agroforestry, 2020)
An experiment was conducted at the research farm of the Department of Forestry & Natural Resources, PAU Ludhiana to compare the effects of inorganic and organic sources of nutrients on productivity of trees and crops in agroforestry system i.e. poplar (Populus deltoides Bartr.) and dek (Melia composita Willd.) with wheat-pearl millet rotation at the age of one, two and three years from 2006-2008. The poplar trees had significantly more height (13.66 m) and dbh (16.87 cm) than the dek trees (height 8.78 m and dbh 13.66 cm) at three-year-age. Light intensity under dek plantation was lower than that of poplar in the second year. The yield of wheat and pearl millet was significantly higher in open than under trees. The application of inorganic nutrients (N and P) significantly increased the wheat grain as well as pearl millet fodder yield compared to organic nutrients (FYM, Vermicompost and FYM + Vermicompost). The increased number of tillers, ear length and 100 grain weight contributed significantly towards higher grain yield of wheat with inorganic fertilizers. Wheat yield was 4.62 t/ha with vermicompost followed by 4.59 t/ha with inorganic nutrients during second year, both the treatments being statistically at par. During third year, although grain yield was higher (3.35 tlha) under inorganic nutrients but all the treatments were statistically non significant. Amongst the organic treatments, the production of pearl millet (fodder) was the highest (20.3 tlha) with the application of vermicompost followed by FYM + vermicompost (19.9 t/ha) and FYM alone (17.6 t/ha). During second year, the differences amongst all the treatments became non-significant.